Proteomic and structural differences in lumpfish skin among the dorsal, caudal and ventral regions - Patel, Deepti M. (Sci Rep, 2019)
Fish skin is a vital organ that serves a multitude of functions including mechanical protection, homeostasis, osmoregulation and protection against diseases. The expression of skin proteins changes under different physiological conditions. However, little is known about differences in protein expression among various body sites in naïve fish. The objectives of this work is to study potential differences in protein and gene expression among dorsal, caudal and ventral regions of lumpfish skin employing 2D gel based proteomics and real-time PCR and to assess structural differences between these regions by using Alcian blue and Periodic acid Schiff stained skin sections. The proteins collagen alfa-1, collagen alfa-2, heat shock cognate 71 kDa, histone H4, parvalbumin, natterin-2, 40S ribosomal protein S12, topoisomerase A and topoisomerase B were differentially expressed among the three regions. mRNA expression of apoa1, hspa8 and hist1h2b showed significant differences between regions. Skin photomicrographs showed differences in epidermal thickness and goblet cell counts. The ventral region showed relatively high protein expression, goblet cell count and epidermal thickness compared to dorsal and caudal regions. Overall, this study provides an important benchmark for comparative analysis of skin proteins and structure between different parts of the lumpfish body.